Glutaraldehyde-Polymerized Hemerythrin: Evaluation of Performance as an Oxygen Carrier in Hemorrhage Models - Anca D. Stoica; Vlad-Al. Toma; Ioana Roman; Bogdan Sevastre; Florina Scurtu; Radu Silaghi-Dumitrescu (Bioinorganic Chemistry and Applications)
Hemoglobin-based oxygen carriers (HBOCs) have been proposed and tested for several decades for the treatment of hemorrhage. We have previously proposed replacing hemoglobin (Hb) in HBOC with the oxygen-carrying protein hemerythrin (Hr), from marine worms, showing that Hr-based derivatives can perform at least as well or even better than Hb-based HBOC in a range of in vitro assays involving oxidative and nitrosative stress as well as in top-up animal models, where small amounts of Hr- or Hb-HBOC were injected into rats. Here, these experiments are extended to a hemorrhage experiment, in which Hr polymerized with glutaraldehyde, alone or conjugated with human serum albumin, is administered after a loss of 20–30% blood volume. The performance of these preparations is compared with that of Hb-based HBOC measured under the same conditions. Polymerized Hr is found to decrease the survival rate and can hence cannot be used as an oxygen carrier in transfusions. On the other hand, an Hr-albumin copolymer restores survival rates to 100% and generally yields biochemical and histological parameters similar to those of glutaraldehyde-polymerized bovine hemoglobin, with the exception of an acid-base imbalance. The latter may be solved by employing an allogeneic albumin as opposed to the human albumin employed in the present study.